I think geometry will help

Geometry Level 5

Let A A be the point ( 8 , 6 ) (8,6) and D D be the point ( 6 , 4 ) (6,4) . If the length of the shortest path A B C D ABCD can be expressed as a + b \sqrt{a} + b , where B B is the point ( x , 3 ) (x,3) and C C is a point ( x , 0 ) (x,0) . This path consists of three connected segments, with the middle one vertical.

Find the value of a b a - b .


The answer is 50.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Oct 27, 2016

The shortest path A B C D ABCD is one that A B AB is a mirror (horizontal) reflection of C D CD , that is:

8 x 6 3 = x 6 4 0 4 ( 8 x ) = 3 ( x 6 ) 7 x = 50 x = 50 7 \begin{aligned} \frac {8-x}{6-3} & = \frac {x-6}{4-0} \\ 4(8-x) & = 3(x-6) \\ 7x & = 50 \\ \implies x & = \frac {50}7 \end{aligned}

Therefore, the shortest path is given by:

l m i n = ( 8 x ) 2 + ( 6 3 ) 2 + ( 3 0 ) + ( x 6 ) 2 + ( 0 4 ) 2 = ( 8 50 7 ) 2 + 9 + 3 + ( 50 7 6 ) 2 + 16 = 36 49 + 9 + 3 + 64 49 + 16 = 477 49 + 3 + 848 49 = 3 7 53 + 3 + 4 7 53 = 53 + 3 \begin{aligned} l_{min} & = \sqrt{(8-x)^2+(6-3)^2} + (3-0) + \sqrt{(x-6)^2+(0-4)^2} \\ & = \sqrt{\left(8-\frac {50}7 \right)^2+9} + 3 + \sqrt{\left( \frac {50}7 - 6 \right)^2+16} \\ & = \sqrt{\frac {36}{49}+9} + 3 + \sqrt{\frac {64}{49}+16} \\ & = \sqrt{\frac {477}{49}} + 3 + \sqrt{\frac {848}{49}} \\ & = \frac 37 \sqrt{53} + 3 + \frac 47 \sqrt{53} \\ & = \sqrt{53} + 3 \end{aligned}

a b = 53 3 = 50 \implies a - b = 53-3 = \boxed{50}

You just read my mind...

Archit Tripathi - 4 years, 7 months ago

How do I prove that the shortest path comprises of a mirror reflection?

Atomsky Jahid - 4 years, 2 months ago

Log in to reply

Sorry, I didn't notice this comment. Check out Heron's shortest distance problem .

Chew-Seong Cheong - 4 years, 2 months ago

Please explain the first statement..

Vishal Yadav - 4 years, 2 months ago

Log in to reply

The shortest distance is one that is traveled by light, therefore, it is a mirror reflection. Read Heron's shortest distance problem for reference.

Chew-Seong Cheong - 4 years, 2 months ago

S h o r t e s t d i s t a n c e i s b y l i n e s t h a t m a k e b i g g e s t ( + / ) a n g l e w i t h v e r t i c a l o r h o r i z o n t a l w i t h i n t h e g i v e n c o n s t r a i n s . B u t B C i s g i v e n a s 3 u n i t v e r t i c a l . F o r s h o r t e s t , a s f a r a s p o s s i b l e , a l l s l o p i n g l i n e s m u s t b e e q u a l l y i n c l i n e d t o y = 0. ( + o r ) H o r i z o n t a l d i s t a n c e b e t w e e n A a n d D , H A D = 2. L e t H A B = m , s o H D B = ( 2 m ) . S o s l o p e o f A B = 3 / m a n d t h a t o f C D = 4 / ( 2 m ) , a n d t h e y m u s t b e e q u a l . S o 3 / m = 4 / ( 2 m ) = 7 / 2 ( b y r a t i o r u l e s ) . m = 6 / 7. S o t o t a l l e n g t h i s A B + B C + C D S i n c e A B a n d C D a r e e q u a l l y i n c l i n e d t o y = 0 , = ( H A B + H B D ) 2 + ( V A B + V B D ) 2 + B C = ( 6 / 7 + 8 / 7 ) 2 + ( 3 + 4 ) 2 + 3 = 2 2 + 7 2 + 3 = 53 + 3 = a + b S o a b = 50 \color{#20A900}{Shortest ~distance ~is~ by ~lines~ that ~make~ biggest ~(+/-) ~angle~ with ~vertical ~or ~horizontal ~within~ the ~given~ constrains. } \\ But~ BC~ is ~given~as~ 3~ unit ~vertical. \\ For~ shortest,~ as~far~as~possible,~ all ~ sloping ~lines ~must~ be ~equally~ inclined ~to~ y=0.~ (+ or -) \\ ~~~~~\\ Horizontal~ distance~ between~ A ~and~ D,~ H_{AD}~=~2.\\ Let ~H_{AB}= m, ~so~H_{DB}=(2-m). \\ ~~~~\\\\\ \color{#3D99F6}{So~ slope ~of~ |AB| = 3/m~ and~ that~ of~ |CD| =4/(2-m),~ and ~}\\ { \Large{they ~must~ be~ equal.} } \\ So~ 3/m= 4/(2-m)=7/2~ (by ~ratio~ rules). \\ \implies~ ~m=6/7. \\ So~ total ~length~ is ~ AB+BC+ CD \\ ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~Since~AB~and~CD~are~equally~inclined~to~y=0, \\ =\sqrt{(H_{AB} + H_{BD})^2 +(V_{AB} + V_{BD})^2 } + B C \\ =\sqrt{(6/7 + 8/7)^2+(3 + 4)^2} + 3 \\ = \sqrt{2^2 + 7^2} + 3 \\ = \sqrt{53} + 3\\ = \sqrt{a} + b\\ So~a-b=\Large \color{#D61F06}{50} \\

Niranjan Khanderia - 1 year, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...